A new method to prepare color-changeable smart packaging films based on the cooked purple sweet potato. (April 2023) - Li, Chenchen; Sun, Jian; Yun, Dawei; Wang, Zeyu; Tang, Chao; Liu, Jun
Abstract: Purple sweet potato (PSP) is an anthocyanins-enriched nutritional food. In this study, a new method was developed to prepare color-changeable smart packaging films based on the cooked PSP. The raw PSP was firstly subjected to steaming, boiling and roasting. The cooked PSP was powdered and then directly used to prepare color-changeable films. The microstructures, physical and functional properties, and practical application of the films were measured. Results showed steaming and boiling treatments were beneficial to retain anthocyanins in PSP, whereas uncooked and roasting treatments were detrimental to maintain the stability of anthocyanins. As compared with the uncooked PSP film and roasted PSP film, the steamed PSP film and boiled PSP film presented more even microstructures and higher crystallinity. Meanwhile, the steamed PSP film and boiled PSP film had stronger barrier ability, mechanical property, thermal stability, antioxidant activity, pH-/ammonia-sensitivity. When applied in the smart packaging of shrimps, the steamed PSP film and boiled PSP film changed their purple color to blue-violet color. However, the reddish-brown color of the uncooked PSP film and roasted PSP film only deepened during the chilled storage of shrimps. Results suggested the steamed PSP film and boiled PSP film had good potentials in smart packaging. Graphical abstract: Image 1 Highlights: Color-changeable films were made using the cooked purple sweet potato (PSP). Steaming and boiling treatments were beneficial to retain anthocyanins in PSP. Steamed and boiled PSP films had more even microstructures and higher crystallinity. Steamed and boiled PSP films had better barrier and color changing properties. Steamed and boiled PSP films were suitable to indicate the freshness of shrimps.